Colonial Roots and Postcolonial Realities of English Language Domination: Akar Kolonial dan Realitas Pascakolonial dari Dominasi Bahasa Inggris - Jasim, Mohammed Younis; Jabar, Maitham Abdalkedhir; Saeed, Mustafa Muslim; Salman, Ahmed Rawdhan (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The global expansion of the English language is historically rooted in the rise of the British Empire, where English functioned as a key mechanism for governance and cultural domination. Specific Background: Within colonial contexts, English was institutionalized through administration, education, and legal systems, contributing to the marginalization of indigenous languages and the creation of socio-economic hierarchies. Knowledge Gap: While previous studies have examined English as a colonial tool, limited research systematically synthesizes its dual role as both a mechanism of control and a site of cultural negotiation in postcolonial societies. Aims: This study aims to critically analyze the historical deployment of English in British colonies and its enduring linguistic and cultural effects, particularly through a comprehensive literature review. Results: Findings indicate that English facilitated colonial cohesion and elite formation while suppressing linguistic diversity. However, colonized populations exhibited agency by developing hybridized English varieties, such as Indian and Nigerian English. Novelty: The study offers an integrated framework that connects colonial linguistic policies with contemporary language use, emphasizing both oppression and adaptation. Implications: Recognizing the legacy of linguistic imperialism is vital for informing equitable language policies that balance global engagement with the preservation of indigenous languages and identities. Highlights: English spread through colonial rule, shaping governance, education, and identity. Analyze English’s colonial role and its postcolonial linguistic-cultural impacts. Inform language policy balancing global English use and local language preservation. Keywords: English language hegemony, British colonialism, linguistic colonialism, cultural identity, linguistic diversity.